2005
DOI: 10.1111/j.1399-6576.2005.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Response Entropy™ is not more sensitive than State Entropy™ in distinguishing the use of esmolol instead of remifentanil in patients undergoing gynaecological laparoscopy

Abstract: In patients undergoing gynaecological laparoscopic day-case surgery, RE seems not to be more sensitive than SE in guiding the use of opioids during general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…15 We have shown, however, that in spite of high doses of esmolol, remifentanil is more effective in obtunding the haemodynamic response to pneumoperitoneum. 16 Thus, irrespective of the mechanisms, the phenomenon may be linked to the nociception.…”
Section: Discussionmentioning
confidence: 99%
“…15 We have shown, however, that in spite of high doses of esmolol, remifentanil is more effective in obtunding the haemodynamic response to pneumoperitoneum. 16 Thus, irrespective of the mechanisms, the phenomenon may be linked to the nociception.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RE−SE difference may indicate nociception or inadequate anaesthesia, an assumption supported by one recently published article, 8 but disputed by another. 9 …”
mentioning
confidence: 99%
“…Patient movement, a clinical sign of inadequate analgesia during or after tracheal intubation, was observed in patients receiving esmolol, whereas in a previous study no movement was observed in the patients receiving remifentanil. 13 These findings suggest that the antinociceptive effect of b1-adrenoceptor antagonists is weaker than that of remifentanil or, because b1-adrenoceptors are present in various parts of the reticular activating system, the effect-site of b1-adrenoceptor-mediated antinociception may differ from that of remifentanil.…”
Section: Discussionmentioning
confidence: 89%
“…Little is known, however, about the effect of b1-adrenoceptor antagonists on the entropy index responses to tracheal intubation. 13 In the present study, we investigated the effect of landiolol on BIS and entropy index responses to tracheal intubation in a double-blind manner. We hypothesized that entropy indices, and BIS, increase in response to tracheal intubation and that the antinociceptive effect of landiolol, observed as a reduction in the RE2SE response, suppresses the arousal response to tracheal intubation.…”
mentioning
confidence: 99%